Morphological and molecular data in the study of the evolution, population genetics and taxonomy of Rhizostomeae - Gamero-Mora, Edgar; Lawley, Jonathan W.; Maronna, Maximiliano M.; Stampar, Sérgio N. [UNESP]; Muhlia-Almazan, Adriana; Morandini, André C. (Elsevier, 2024)
Rhizostomeae research based on morphological approaches was reinforced and diversified by new techniques after the 1970s, including developing methodologies for phylogenetic analysis, the rise of the polymerase chain reaction, and the emergence of different sequencing technologies. Here, we summarize the contribution of morphological and molecular data to the study of the classification and phylogenetic relationships of Rhizostomeae in addition to the use of molecular data in studies at the population, species, and supraspecific levels. Throughout the history of the study of the Rhizostomeae systematics, morphological data have been neglected when it comes to phylogenetic inferences, which is reflected in the lack of a phylogenetic analysis of the taxa within Rhizostomeae based on phenotypic characters of the adult medusa. Concerning molecular data, ca. 3,200 nucleotide sequences are available in GenBank and are mainly used for discovering, delimiting, describing, and identifying species. Molecular approaches have also allowed species monitoring by qPCR and metabarcoding of environmental DNA, as well as unveiling the distribution and genetic diversity of jellyfish populations, shedding light on introduction events, conservation, and health of edible jellyfish stocks. Nucleotide sequences have also been key for the development of phylogenetic hypotheses that serve as basis for investigations on the origin and diversification of morphological, ecological, and behavioral traits within Cnidaria; however, despite the progress achieved, phylogenetic uncertainty still exists, especially within the formerly known superfamily Inscapulatae. Future directions in Rhizostomeae research involve generating molecular and morphological data of neglected taxa, which represents a golden opportunity to understand the evolution of Rhizostomeae.
Keywords: Cnidaria; Jellyfish; Medusozoa; Phylogenetic systematics; Scyphozoa